Apakah Dana Pihak Ketiga dan Tatakelola Yang Baik Dapat Meningkatkan Kinerja Bank Syariah Dalam Perspektif Nasabah? - Nurimani, Munadiya; Mardian, Sepky; Maulidha, Erina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This research aims to test the effect of third-party funds and good corporate governance on the performance of Islamic banks in the customer's perspective. From the customer perspective, the performance of Islamic banks is proxied by the level of profit-sharing for depositors. With the positivism paradigm, the sample data of Islamic commercial banks selected based on the availability of governance reports is processed using regression panel data. Fixed effect model is a selected model that is also validated based on the classic assumption test. This research finding can explain that the better the company's governance, the better the performance of Islamic banks. The implementation of effective corporate governance can safeguard the interests of customers and shareholders. This finding further strengthens the argument for the urgency of governance in improving the performance of Islamic banks. But the large level of third-party funds cannot afford to be a control over revenue sharing increases for the investment account holder. This finding has implications that Islamic bank management must be more consistent in implementing effective corporate governance for the benefit of customers and shareholders.